Factors Affecting the Level of Compliance with Medication in Diabetes Mellitus Patients Treated at the Service Foundation Medical Center Kasih A dan A Rahmat Waingapu - Uly Agustine; Leonardo Ronel Ralf Welem (Poltekkes Kemenkes Kupang, 2018)
Background: Diabetes Mellitus (DM) is a disease with high blood sugar levels caused by insulin deficiency in the blood that occurs due to damage to pancreatic beta cells. Data from Health Department of East Sumba Regency indicate the number of DM patients in 2015 amounted to 764 patients, while in 2016 (January-November) as many as 561 patients. The purpose of this study is to identify factors that affect the level of adherence of medication to DM patients including age, gender, education, occupation, knowledge. Method: This research uses descriptive method. Sampling technique Total Sampling. The instrument used in this study is a questionnaire and an observation sheet involving 25 people with DM patients. Result: From the result of the research, the respondent's distribution is based on the age of the respondent, the most is 45-59 years old is 12 people (48%), based on sex of the most sex of women is 19 people (76%), based on the most education Is 11 elementary school students (44%), based on work which do not work the most that is working amounted to 13 people (52%), based on the most knowledge is knowledge less as much as 9 people (36%), and result of sheet Observation of compliance level of respondents who obedient only 6 people (24%) while non-compliance as much as 19 people (76%). Conclusion: To ensure patient compliance in taking DM medication, it is necessary to supervise the medication and explain about the importance of taking medication regularly and the need for home visit activity by medical center for follow up of DM patient.